ANALISIS RESILIENSI SISWA SMA DI KOTA TOMOHON DALAM MASA PANDEMI COVID-19 - Kumaat, Theophany D; Tiwa, Tellma M; Sengkey, Stevi B (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The Covid-19 pandemic affects most of the aspects in our life. Resilience is the ability of maintaining self during hard time and how to raise after the hard time. Subject of this research are 300 high school student, age 15-18, lives in Tomohon, and Study from Home during Covid-19 pandemic. The questionnaire was shared using social media, and the sample was taken using snow ball technique. The data was analysed using t-test dan one way anova. The result shows that 48% of the subject have medium level of resilience, and the lowest 3% of the subject have low level of resilience